2004
DOI: 10.1103/physrevlett.92.040801
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic Mechanism of NaCl Nucleation from an Aqueous Solution

Abstract: Despite great technological relevance, the initial steps of nucleation and crystal growth from solution are still poorly understood. While experimentally difficult to access, simulations in principle may provide insight at the atomic level. However, in most cases the computational demand dramatically exceeds the scope of current hardware. Since crystallization usually occurs on time scales much larger than the few ns of a molecular dynamics simulation, special techniques for the study of rare events are of par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
147
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 144 publications
(152 citation statements)
references
References 17 publications
3
147
0
2
Order By: Relevance
“…Such level of modeling, arguably most realistic, is computationally demanding, so a special technique was used to sample the phase space more efficiently. 24 Small ion clusters were observed that were interpreted as stable precursors of NaCl nanocrystals.…”
Section: Introductionmentioning
confidence: 99%
“…Such level of modeling, arguably most realistic, is computationally demanding, so a special technique was used to sample the phase space more efficiently. 24 Small ion clusters were observed that were interpreted as stable precursors of NaCl nanocrystals.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, molecular simulations play an important role and much work has been devoted to the study of homogeneous nucleation in simple model systems like Lennard-Jones particles or hard spheres (1)(2)(3). More recently, growing attention has been paid to the computer simulation of nucleation from solution of organic and inorganic materials (4)(5)(6)(7)(8)(9)(10)(11).…”
mentioning
confidence: 99%
“…Interestingly, alteration of Lennard-Jones parameters has been used to initiate a nucleation process for NaCl that was subsequently investigated by using the path sampling method developed by Chandler and co-workers. 60 The authors modified the ion-water interactions to obtain an artificial system that crystallizes in a few tens of picoseconds. Hence, nucleation could be studied from simulations generated by using AMBER parameters.…”
mentioning
confidence: 99%